What is English and why should we care? - Machan, Tim William (Oxford, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and index
Keywords: English language -- History; English language -- Social aspects; Ngôn ngữ Anh -- Lịch sử; Ngôn ngữ Anh -- Khía cạnh xã hội